Art History and Its Publishers. - Holly, Michael Ann; Ledbury, Mark; Armato, Douglas; Bielstein, Susan; Brown, Andrew; Conover, Roger; Constantinopoulos, Vivian; Fay, Stephanie; Pabbruwe, Herman; Soussloff, Catherine M.; Wissoker, Ken; Scott, Curtis (Art Journal)
The article presents the views of several publishers and editors of major U.S. and European presses to talk through the many changes and challenges facing publishing in the visual arts, the role of publishing within the field today, and the always shifting commercial and political terrain on which it takes place. They include Roger Conover, Douglas Armato and Susan Bielstein.